The Effectiveness of Marriage Construction and Construction Agency in Minimizing the Rate of Divorce in Pariaman City West Sumatera - Sobhan, Sobhan; Kholidah, Kholidah; Ridho, Muhammad (Jurnal Dinamika Hukum, 2022)
The increasing divorce rate in Pariaman City is a sign for the functioning of the agency tasked with providing counseling and training to maintain marriage and keep the household in harmony, this increase in divorce can be seen from 2010 to 2021 which is a significant increase. Answering these problems, descriptive qualitative research methods are used which give the results that there are many factors for divorce and efforts to improve the quality of the Pariaman City Advisory Board for Marriage Development and Preservation, such as internal and external aspects. And one of the important formats is formulating the Effectiveness of BP4 in Efforts to Minimize the Divorce Rate with its indicators Clarity of goals to be achieved, Clarity of strategy for achieving goals, Preparation of appropriate programs and a good plan, Availability of work facilities and infrastructure, Education supervision and control system.Keywords: Effectiveness; Advisory Board for the Development and Preservation of Marriage; Divorce Rate; Pariaman City.